(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Eugene O’Neill is one of the greatest modern dramatists. His Drama presents a psychological study of the working of human mind and societyhumanity. He transformed the conflict between man and God or man and nature dramatized in Greek tragedy into a struggle within the suffering individual. O’Neill’s attempt was to deal with the conflict between man’s reality and his dope-dreams, i.e. his being in bad faith. In O’Neill, like in Sartre, bad faith is an attempt to stay put in the unconscious. Though the unconscious is an autonomous force, independent of individual man, it is not cut off from the conscious. Our approach to the unconscious post-dates Freud, in which the unconscious and the conscious co-exist, and in essence, bad faith is another name for the unconscious. Though O’Neill, in his plays, tries to extricate the conscious from the bad faith in which his characters often wallow, not to show that we should completely ignore the tendency to relapse, but to show that the conscious must not submit completely to the dope-dreams, because it then causes a complete withdrawal from reality and action, and similarly a complete suppression of the conscious.So, throughout his life, as O’Neill’s plays reveal, man is forced to wrestle with the bad faith of pipe-dreams and self-lies. If either of the two is ignored, the outcome would be the loss of self or of the existence. So, O’Neill’s solution to the relapse into the bad faith, the past, pipe-dreams, self-lies is that man must asserts self-knowledge, and give up lying to oneself as early as possible, so as to become his authentic self, whatever it costs.